Babar's yoga for elephants - Brunhoff, Laurent de, 1925- (Harry N. Abrams, 2002)
Babar the elephant demonstrates and provides step-by-step instructions for basic yoga techniques and positions, then shows how he and Celeste use them to relax and have fun as they travel around the world.